Hepatic blood inflow occlusion without hemihepatic artery control in treatment of hepatocellular carcinoma - Jin, Shan (Baishideng Publishing Group Co., Limited, 2010)
AIM: To investigate the clinical significance of hepatic blood inflow occlusion without hemihepatic artery control (BIOwHAC) in the treatment of hepatocellular carcinoma (HCC). METHODS: Fifty-nine patients with HCC were divided into 3 groups based on the technique used for achieving hepatic vascular occlusion: group 1, vascular occlusion was achieved by the Pringle maneuver (n = 20); group 2, by hemihepatic vascular occlusion (HVO) (n = 20); and group 3, by BIOwHAC (n = 19). We compared the procedures among the three groups in term of operation time, intraoperative bleeding, postoperative liver function, postoperative complications, and length of hospital stay. RESULTS: There were no statistically significant differences (P > 0.05) in age, sex, pathological diagnosis, preoperative Child’s disease grade, hepatic function, and tumor size among the three groups. No intraoperative complications or deaths occurrred, and there were no significant intergroup differences (P > 0.05) in intraoperative bleeding, hepatic function change 3 and 7 d after operation, the incidence of complications, and length of hospital stay. BIOwHAC and Pringle maneuver required a significantly shorter operation time than HVO; the difference in the serum alanine aminotransferase or aspartate aminotransferase levels before and 1 d after operation was more significant in the BIOwHAC and HVO groups than in the Pringle maneuver group (P < 0.05). CONCLUSION: BIOwHAC is convenient and safe; this technique causes slight hepatic ischemia-reperfusion injury similar to HVO.